Utilization of Green Belts to Woodland Tourism in Support the Development of the Ecotourism at Serbaguna Wonogiri Dams. (April 2018) - Prabowo, S F D; Muryani, C; Utomowati, R
Abstract: This research aims to identified: (1) the potential location for developed to woodland tourism, (2) obstacles development woodland tourism, (3) direction development of green belts to woodland tourism in support the development of the ecotourism at Serbaguna Wonogiri Dams. The data were collected by field observation and analysis laboratory then matching between the land's quality on the condition growing plants in accordance with their condition land to determine plant will cultivated and benefits for conservation reservoir. Data analysis are using descriptive qualitative. The results of the research shows that: (1) there are 6 classes of potential location which are able to be developed as woodland tourism, (2) obstacles found is the lack of public participation in change agricultural land rent to woodland, the majority of green belt in western many have become settlement, accessibility is bad, (3) directions development are educate the community about the importance of sustainability green belts against reservoirs and increase accessibility.